Digitalisasi Pendidikan Melalui Pengembangan Media Digital Interaktif Tema Alam Semesta untuk Memfasilitasi Keterampilan Saintifik Anak Usia Dini - Rahmawati, Febi; Mulyana , Edi Hendri; Qonita, Qonita (Fakultas Tarbiyah dan Keguruan UIN Antasari Banjarmasin, 2024)
The development of the 21st century has sparked digitalization in all aspects of life, including in the field of education. The implementation of digital learning using digital learning media in the field is still very minimal, this is due to the lack of access to digital learning that is in accordance with learning objectives, such as science learning which is oriented towards developing scientific skills. The minimal use of digital media makes researchers conduct research with the aim of obtaining media designs that are suitable for the development of scientific skills in early childhood. The subjects of this research were four PAUD institutions consisting of four teachers and 60 group B children. This research was carried out using a mix method approach, using the Reeves 2006 EDR (educational design research) research model. The data collection techniques used included observation, interviews, and questionnaires. The results of the research show that teachers are currently unable to maximize efforts to digitize education, this is due to the lack of access to digital media in science learning which is oriented towards developing children's scientific skills. This series of research also produces a valid media storyboard design based on the assessment of media experts and material experts, namely with an average score of 2.78 and 2.92 in the Very Good category respectively.